An Analysis of English Textbook for Junior High School Students Based on Curriculum Relevance and Language Skills Development - Nur Mashlihah; Nurhijjah Nelly Waty Siregar; Nurlatifah; Tias Hadaning; Sarah; Elyza Martiarini (International Journal of Technology and Education Research, 2026)
This study aims to analyze English textbooks for junior high school students based on curriculum relevance and language skill development. The study employed a qualitative approach using library research. Data were obtained from various scientific articles published between 2021 and 2025, discussing English textbook analysis, curriculum suitability, and the development of listening, speaking, reading, and writing skills. Data collection was conducted through a literature search in academic databases, then analyzed using content analysis techniques through the stages of identification, classification, evaluation, and synthesis of research findings. The results indicate that, in general, junior high school English textbooks align with the requirements of the applicable curriculum. The material presented encompasses contextual themes, clear learning objectives, and the integration of character values ​​and language competencies. Textbooks also accommodate the four language skills, although their distribution is not balanced. Reading and writing skills receive a more dominant portion than listening and speaking skills. Furthermore, it was found that activities that encourage critical thinking, creativity, and project-based learning are still limited. This study concludes that junior high school English textbooks are well-relevant to the curriculum, but still require further development to optimally balance language skills and 21st-century competencies. The research findings are expected to serve as evaluation material for teachers, textbook authors, and curriculum developers in improving the quality of English teaching materials.